Tree Species Distribution and Diversity in Kibonge Forest Reserve, Kenya - Chirchir, E.; Sudoi, V.; Kimanzi, J. (Africa Environmental Review Journal, 2018)
Many forests are under great anthropogenic force and require management interventions to protect and maintain the overall biodiversity and productivity. Understanding species diversity and distribution patterns is important for assisting managers evaluate the complexity and resources of these forests. Tree species distribution and diversity were assessed in Kibonge Forest Reserve. Data were collected between, July 2013 and July 2014 using quantitative vegetation analysis method on trees samples of DBH limit of ≥15 cm. Tree parameters; species, trees size (diameter at breast height (DBH)), total height and amount of canopy cover were determined within eighty seven (87) systematically located vegetation plots of size 20 by 10m along three transect lines. A total of 1124 trees were measured and 29 tree species were identified in the study area. Data obtained were analyzed using descriptive, Chi square tests and Cross tabulation analysis. Tree species were identified in the field while those which could not be identified had their essential parts pressed and taken to a university herbarium for identification .Chi square tests were carried out to establish variations between species and altitude. The dominant tree species in the forest were C. lustanica (39%), Dombeya goetenzii (24%), Prunus africana (11.3%), Croton macrostachyus (9.2%) and M. kilimandascharica (6.8%). The basal area estimated is 23.85m2 while the population density was 2trees/Ha. Results showed that more tree species were concentrated on altitude 2400m (χ2=610.95, df =78, p<0.001). Having known that the population of trees is low, there was need to establish an intense programme of re afforestation and to protect further reduction the existing forest by creating buffer zones on boundaries between human habitation and the forest.